Health Education Using Booklet to Increase Knowledge on Anemia among Adolescent Girls - Endah Yulianingsih; Febri Dwi Yanti; Dinda Hulawa (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2023)
Iron deficiency is one of the healthful issues in Asia, remembering for Indonesia. Young women often consume risky foods such as fast food, snacks and soft drinks. Such condition is due to lack of education among adolescent girls. This study aims to determine the effect of health education using booklet media on the increase in knowledge on anemia among adolescent girls. This was a pre-experimental study with a One-Group Pre-Test-Post Test Design approach. The population involved in this study was adolescent girls in State JHS of Gorontalo City, with a total sample of 132 respondents. The samples were selected using the Simple Random Sampling technique. Data on knowledge were derived from questionnaires that had been tested for validity and reliability. The study was conducted in February to March 2021. Data analysis was performed using the Wilcoxon test. The results showed that there was an effect of health education using booklet media on the increase in knowledge on anemia among adolescent girls with p-value equals 0.000. It is expected that healthcare workers can provide health services in the form of education to young women using booklet media so that adolescents are interested in listening to information and the information can be easily understood.